Experimental optical phase measurement approaching the exact Heisenberg limit. Issue 1 (December 2018) - Daryanoosh, Shakib; Slussarenko, Sergei; Berry, Dominic; Wiseman, Howard; Pryde, Geoff
Abstract The use of quantum resources can provide measurement precision beyond the shot-noise limit (SNL). The task of ab initio optical phase measurement—the estimation of a completely unknown phase—has been experimentally demonstrated with precision beyond the SNL, and even scaling like the ultimate bound, the Heisenberg limit (HL), but with an overhead factor. However, existing approaches have not been able—even in principle—to achieve the best possible precision, saturating the HL exactly. Here we demonstrate a scheme to achieve true HL phase measurement, using a combination of three techniques: entanglement, multiple samplings of the phase shift, and adaptive measurement. Our experimental demonstration of the scheme uses two photonic qubits, one double passed, so that, for a successful coincidence detection, the number of photon-passes isN  = 3. We achieve a precision that is within 4% of the HL. This scheme can be extended to higherN and other physical systems. Measurements of an unknown optical phase have not yet been performed with the ultimate precision, i.e. saturating the Heisenberg limit. Here, Daryanoosh et al. demonstrate this with a precision within 4% of the Heisenberg limit by combining photonic entanglement and multiple passes.